KONTRIBUSI KELINCAHAN, KESEIMBANGAN DAN KOORDINASI MATA-KAKI DENGAN KEMAMPUAN MENGGIRING BOLA DALAM PERMAINAN SEPAKBOLA SISWA SMA NEGERI 1 PULAU LAUT TENGAH KABUPATEN KOTABARU - Hasruddin _ (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2017)
This research is a descriptive research type. This study aims to determine: (1) To determine whether there is a contribution between agility with the ability to dribble on football games students SMA Negeri 1 Pulau Laut Tengah. (2) To know whether there is a contribution between balance with the ability to dribble on the game of football student of SMA Negeri 1 Pulau Laut Tengah. (3) To know whether there is contribution between the foot with the ability to dribble soccer game at the students of SMA Negeri 1 Pulau Laut Tengah. (4) To find out whether there is contribution between agility, balance and eye-foot coordination with the ability to dribble on football game students of SMA Negeri 1 Pulau Laut Tengah. The population is a student of SMA Negeri 1 Pulau Laut Tengah. The sample used is male students SMA Negeri 1 Pulau Laut Tengah 30 people. The technique of determining the sample is by random selection by drawing method (Simple Random Sampling). Data analysis technique used is descriptive analysis and inferential analysis through program of SPSS 22 at significant level Î± 0,05. The results showed that; (1) there is contribution between agility with dribbling ability in game of soccer student of SMA Negeri 1 Pulau Laut Tengah, equal to 44,7%, (2) To know whether there is contribution between balance with ability dribbling at game of soccer student SMA Negeri 1 Island (3) To find out whether there is contribution between foot-toe and dribbling ability on the game of soccer students of SMA Negeri 1 Pulau Laut Tengah is 30.4%, (4) there is contribution between agility, equilibrium and eye-foot coordination with dribbling ability on football game of students of SMA Negeri 1 Pulau Laut Tengah, with F: 15,987 and sig (p) = 0,000.